Evaluation on growth and production of convergent breeding wheat (Triticum aestivum L.) genotypes adaptive to lowland. Issue 1 (April 2020) - Rafiuddin,; Amin, A R; Nur, A; Farid, M; Sari, A T I
Abstract: This study aimed to determine the genotype of wheat from a convergent breeding program that adaptive to lowland and produce high yield, and determine the parameters with high heritability. The study was conducted at the Screen House of Indonesian Cereals Research Institute (ICERI), Maros Regency from October 2017 to February 2018. The study used a Randomized Block Design with 10 wheat genotypes of convergent breeding crossbreeds including CBF 124, CBF 159, CBF 192, CBF 169, CBF 137, CBF 195, CBF 119, CBF 145, CBF 156 and CBF 231 as well as four comparators, namely two national superior varieties (Selayar and Dewata) and two introduced genotypes (Oasis and HP. 1744) resulted in 14 genotypes. The results show that the genotype of wheat from convergent breeding that adaptive to lowland and had high productivity are CBF 192 (1.80 tons ha −1 ), CBF 169 (1.66 tons ha −1 ), CBF 195 (1.54 tons ha −1 ), CBF 137 (1.44 tons ha −1 ), CBF 124 (1.42 tons ha −1 ) and CBF159 (1.34 tons ha −1 ). Characters that have high heritability are plant height, number of tillers and productive tillers, age of flowering and harvest, panicle length, number of spikelet, number of floret, number of grains on the main panicle and on the tillers, weight of grains on the main panicle and on the tillers, and production.